Peraturan Daerah Dalam Hirarki Perundang-undangan Indonesia - Isroji, Isroji; Anam, Khoirul; Irawan, Andrie; MF, Moh Shofiyul Huda; Rahman, Ahmad Syafii; Fadzlurrahman, Fadzlurrahman (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2024)
Regional regulations in Indonesia which are formed by regional heads of provinces and cities with regional representative councils in equivalent areas have been regulated in such a way that efforts for comprehensive harmonization and synchronization of all aspects must be carried out on an ongoing basis. This prescriptive normative research prioritizes careful literature searches, especially in terms of legislative documents. The formation of a region is not easy because it requires competent insight and expertise, especially regarding the techniques of its formation, so that the regional regulations that are formed do not conflict with the hierarchy of regulations and fulfill the interests of the community in the area of authority.